STUDI KASUS: PERAWATAN PALIATIF KARSINOMA PAYUDARA STADIUM LANJUT MELALUI PENDEKATAN MODEL ADAPTASI ROY: Case Study: Palliative Treatment of Advanced Stage Of Breast Carcinoma Through The Roy Adaptation Model Approach - Tuti Suhertini; Dewi Irawati; Riri Maria (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2023)
Breast cancer patients with advanced stages who have undergone previous cancer treatment require palliative care support in an effort to fulfill their health needs. Mrs. N, a 60 year old woman, with metastatic breast carcinoma of the lung and (suspected) skin, was initially admitted to the ward with further chemotherapy plans. The patient and family decided to move treatment at the Jakarta Hospital from the previous hospital with high hopes of recovery. The patient has extensive breast wounds on the chest to the right abdomen and back. The patient complains of fatigue and pain all over the body with a pain scale of NRS=5. With the current state of the advanced stage, the Doctor in Charge of the Patient (DPJP) decides that the patient will switch treatment goals to palliative care. Researchers use this adaptation model with the aim of helping patients and families recognize health problems faced by looking at humans as a whole (bio-psycho-social) and helping to use positive coping to be able to adapt. The nursing assessment was carried out using Roy's Adaptation Model theory so that the main problems were obtained, namely nutritional deficits and knowledge deficits about palliative management. Nutritional management interventions by maintaining nutritional intake by administering a liquid diet 6x250 cc/day and extra egg whites 2-3 eggs/day through a Naso Gastric Tube (NGT) tube and health education about palliative care provided in collaboration with DPJP, a specialist in internal medicine with a subspecialty of hematology -medical oncology. Implementation is carried out by nurses for 6 days of treatment with evaluation assessments every day. The results showed that the patient's nutritional status improved by maintaining nutritional intake through the provision of food and drink per NGT and patient and family knowledge regarding palliative care increased. Result from this case study, nursing care using Roy's Adaptation Model theory can be applied to the condition of advanced cancer patients with palliative care so that the patient's nursing problems can be resolved properly. .